Orientações pedagógicas no estágio supervisionado de educação física na Colômbia, Brasil, Argentina e Chile - Zuluaga, Carlos Federico Ayala [UNESP] (2015)
This work was research focus Pedagogical Guidelines Degree in Physical Education courses contemplating the scene of the Supervised Internship in Colombia, Brazil, Argentina and Chile. The theoretical foundation focuses on teacher training. As general goal, we seek to understand the Pedagogical guidance of teachers, which the analysis of the locus Supervised Internship in the courses of Physical Education the Colombia, Brazil, Argentina and Chile. Specifically we have the following objectives in this work: a) teachers know the public policy on the Supervised Internship in Colombia, Brazil, Argentina and Chile; b) Pedagogical Guidelines identify the courses of Physical Education, taking as reference the Educational Policy Project; c) point the knowledge that participating teachers of the Supervised Internship they have on Pedagogical Guidelines; and d) analyze how are put into play the Pedagogical Guidelines present in teachers who are part of the supervised training scenario. We chose a qualitative research approach, Historical and Descriptive-Hermeneutic method, multiple case studies, having as technical content analysis, the documentary source tools and semi-structured interview. Among the results, we observe the first known Category Regulation of Supervised Internship (ES) in Colombia, Brazil, Argentina and Chile, taking into account know the different procedures linked public policy in the regulatory framework and institutional field (Universities), which focus on training of students and also commonly in different cultural manifestations of the educational communities. Of the following subcategories emerged: Normative guidelines Supervised Internship and the Supervised Internship in Educational Policy Project; comprising the PPD of government entities respond to requirements for production, it is contrary in universities, which tries to cultivate training for adaptability, reflection, criticism and knowledge building. We build...